Postnatal exposure to ambient temperature and rapid weight gain among infants delivered at term gestations: a population‐based cohort study. Issue 1 (24th December 2021) - Dionicio López, Carlos Francisco; Alterman, Neora; Calderon‐Margalit, Ronit; Hauzer, Michael; Kloog, Itai; Raz, Raanan
Abstract: Background: The global prevalence of childhood obesity has risen dramatically recently. Previous studies found an association between rapid infant weight gain and childhood overweight. Evidence suggests that exposure to high ambient air temperatures during prenatal life and during adulthood is associated with birthweight and obesity respectively. Objective: The objective of this study was to examine whether exposure to high ambient temperatures during infancy is associated with rapid infant weight gain in Israel. Methods: This is a population‐based historical cohort study using data from the Israeli national public network of maternal and child health clinics between 2008 and 2013. We assessed exposure to ambient temperature in the first year of life using a high‐resolution hybrid spatio‐temporal model and calculated annual mean and minimum temperatures for each infant based on daily mean and minimum temperatures at the community clinic location. We defined rapid infant weight gain as a World Health Organization weight z ‐score difference >0.67 between birthweight and weight at age one year. We estimated these associations using log‐linear and general additive models and adjusted for population group, district, maternal age, parental education, parity, sex, gestational age, birthweight, calendar year and calendar month of birth. Results: The study population included 217, 310 singleton‐term infants. Adjusted models demonstrated a positive association between ambient temperature exposure and rapid infant weight gain. Compared to the third quintile of minimum temperature, infants exposed to the first and second quintile had an adjusted relative risk of 0.98 (95% CI 0.96, 1.00) and 0.97 (95% CI 0.95, 0.98), respectively, while those exposed to the fourth and fifth quintiles had an adjusted relative risk of 1.06 (95% CI 1.04, 1.07) and 1.02 (95% CI 1.00, 1.04) respectively. The associations with mean temperature were similar but slightly weaker. Conclusions: Exposure to higher ambient temperatures, of emerging importance in the climate change era, is associated with rapid infant weight gain in Israel. Future studies should use additional exposure, covariate, and outcome data to analyse the nature and the source of this association in more detail.